Paternal Retrieval Behavior Regulated by Brain Estrogen Synthetase (Aromatase) in Mouse Sires that Engage in Communicative Interactions with Pairmates - Akther, Shirin; Huang, Zhiqi; Liang, Mingkun; Zhong, Jing; Fakhrul, Azam A. K. M.; Yuhi, Teruko; Lopatina, Olga; Salmina, Alla B.; Yokoyama, Shigeru; Higashida, Chiharu; Tsuji, Takahiro; Matsuo, Mie; et al. (Frontiers in Neuroscience, 2015)
Parental behaviors involve complex social recognition and memory processes and interactive behavior with children that can greatly facilitate healthy human family life. Fathers play a substantial role in child care in a small but significant number of mammals, including humans. However, the brain mechanism that controls male parental behavior is much less understood than that controlling female parental behavior. Fathers of non-monogamous laboratory ICR mice are an interesting model for examining the factors that influence paternal responsiveness because sires can exhibit maternal-like parental care (retrieval of pups) when separated from their pups along with their pairmates because of olfactory and auditory signals from the dams. Here we tested whether paternal behavior is related to femininity by the aromatization of testosterone. For this purpose, we measured the immunoreactivity of aromatase (cytochrome P450 family 19 (CYP19)), which synthesizes estrogen from androgen, in nine brain regions of the sire. We observed higher levels of aromatase expression in these areas of the sire brain when they engaged in communicative interactions with dams in separate cages. The capacity of sires to retrieve pups was increased following a period of five days spent with the pups as a whole family after parturition, whereas the acquisition of this ability was suppressed in sires treated daily with an aromatase inhibitor. These results suggest that brain aromatization regulates the initiation, development, and maintenance of paternal behavior in the ICR mice.